Trichoderma species as Biocontrol Agent against Soil Borne Fungal Pathogens - Bastakoti, Srijana; Belbase, Shiva; Manandhar, Shrinkhala; Arjyal, Charu (Nepal Journal of Biotechnology, 2017)
Soil borne pathogenic fungi are of major concern in agriculture which significantly decreases the plant yield. Chemically controlled plant imposes environmental threats potentially dangerous to humans as well as other animals. Thus, application of biological methods in plant disease control is more effective alternative technique. This study was carried out to isolate Trichoderma species from soil sample and to assess its in vitro biocontrol efficacy against fungal pathogens viz. Sclerotium rolfsii, Sclerotionia sclerotiorum, Fusarium solani and Rhizoctonia solani. Biocontrol efficacy testing of isolates against different fungal pathogens was performed by dual culture technique.In this study, 5 different Trichoderma species were isolated from 26 various soil samples and were tested against four fungal soil-borne pathogens. Inhibition percentage of radial growth of Sclerotium rolfsii by three of the Trichoderma isolates was found to be 100%; about 62% and 68% of maximum inhibition was observed against Rhizoctonia solani and Fusarium solani respectively whereas Sclerotionia sclerotiorum was inhibited maximum up to 23%. This in vitro study revealed that although Trichoderma species plays an important role in controlling all type of soil borne fungal plant pathogens, however, isolates as biocontrol agent against Sclerotium rolfsii was found to be more efficient in comparison to other pathogens.Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1: 39-49